THE HIERARCHY OF THE PURPOSES OF PRE-SCHOOL AND PRE-PRIMARY EDUCATION IN LITHUANIA - Ruškus, Jonas; Žvirdauskas, Dainius (Acta Paedagogica Vilnensia, 2010)
This article analyses the findings of an empirical study carried out in Lithuania. The aim of this study was to determine transsubjective understanding of the purpose of pre-school and pre-primary education, and to evaluate how the participants of education – pedagogues, children’s parents, and specialists – perceive different purposes of such education. The study was based on two theoretical perspectives: the paradigm of child centered education, and the concept of community management. A quantitative written questionnaire-based inquiry of the participants of pre-school and pre-primary education was performed, consisting of 14 socio-demographic items (independent variables) and 44 content items (dependent variables). In total, 4,690 filled questionnaires were received from 79 pre-school and pre-primary educational institutions. Factor analysis was performed in order to validate the reliability and validity of the findings, and to group the dependent variables. Pre-school and pre-primary education in Lithuania is experiencing contradictions between the purposes and the real life. These contradictions are systemic, since they are characteristic more of the system of pre-school and pre-primary education rather than individual persons or institutions. The majority of the participants of pre-school and pre-primary education (pedagogues, children’s parents, and specialists) were satisfied with the assurance of the minimal of children’s education – i.e. the most important thing for them was that the children were occupied and safe under the supervision of people with educational experience and qualification – the pedagogues. A large part of the parents were oriented towards the competition-based model of education. The parents exerted pressure on the pre-school and pre-primary educational institutions to ensure that these institutions prepared their children for school by teaching writing, reading, and the ability to successfully compete for the “place under the sun”. According to such parents, the purpose of pre-school and pre-primary educational institutions is their children’s preparation for school rather than the development of their dignity, self-perception, and self-determination. Only the parents from groups that are seen as alternative to the traditional ones strongly expressed the principles of child-oriented pedagogy and rejected those of the adult-dominated pedagogy, although these groups were not very similar in other value-based aspects. The absence of the child’s voice – also called the child’s perspective or vision – in kindergartens is an especially problematic issue. The parents and the pedagogues did not see a child’s opinion as important in making decisions concerning the aims and the organization of education. The children neither have the power to participate in the decision-making processes nor are they seen as experts of their situation.